Modeling and simulations of fuel cell systems for combined heat and power generation. (25th May 2016) - Kang, Kyungmun; Yoo, Haneul; Han, Donghee; Jo, Ahrae; Lee, Junhee; Ju, Hyunchul
Abstract: Combined heat and power (CHP) fuel cell systems have been under development for the past several decades to enable distributed power generation. These fuel cell systems consist of several subsystems, such as a fuel cell stack, a fuel processing system, heat exchangers, and a heat recovery system. Optimal integration of these subsystems is critical to develop highly efficient, cost effective fuel cell systems for CHP generation. In this paper, we describe the system modeling of a 20 kW fuel cell system, in which a PEM fuel cell stack is connected with fuel processors, i.e., a steam reformer with water gas shift and preferential oxidation reactors. The model is implemented within a commercial flow-sheet simulator, ASPEN HYSYS. We also analyze the effects of key operating parameters on the electrical and thermal efficiency of the 20 kW power systems. The simulation results indicate that the fuel delivery rate and air-fuel ratio supplied into the burner are major control factors to achieve a net electrical power of 20 kW and an acceptable CO concentration level (<10 ppm). Highlights: The fuel-cell-based CHP system is modeled and simulated. The use of high y values leads to insufficient hydrogen yield. The CO fraction is maintained at a low concentration due to the high level y values. The heat flux from the burner is sensitive to the level of AFR.